INHERITANCE OF RESISTANCE TO Papaya ringspot virus IN WATERMELON - Silveira, Lindomar Maria da (2015)
Aiming to study the genetic control of Papaya ringspot virus, type watermelon (PRSV-W) in watermelon, the cultivar Crimson Sweet (P1 – susceptible) and L26 derived from PI 244019 (P2 – resistant), as well as the resulting populations F1, F2, RC11 and RC21 of the cross of both lines were evaluated. The trials were carried out in a greenhouse, and the evaluations were done using artificial inoculations with PRSV-W isolates. The seedling symptoms were recorded using a graded scale, and the serological evaluation was done with specific antiserum using indirect ELISA. The estimated variances of the populations were used to obtain the genetic (σ2G), the environmental (σ2E), phenotypic (σ2F2), additive (σ2A) and dominance (σ2D) variances as well as the broad (h2a) and narrow sense (h2r) heritabilities. The hypothesis of monogenic inheritance was tested under different presumed average degrees of dominance as well as using the maximum likelihood. The distribution of resistant plants in the segregating populations was different from a distribution based on monogenic inheritance for all presumed average degrees of dominance, therefore, the hypothesis of monogenic inheritance was rejected indicating that this character in the line L26 is controlled by more than one major gene with the presence of modifiers. The additive-dominant model was adequate to explain the type of gene action involved, and the epistatic effects were not important in the expression of the resistance. The estimated average degree of dominance indicated complete dominance. The broad sense heritabilities for the two variables analyzed were intermediate.